Towards an in-depth view of the reproductive biology of Schistosoma mansoni : from gonad isolation to sub-transcriptomics and cell culture - Lu, Zhigang; Justus Liebig University Giessen (My University, 2015)
Schistosomiasis remains a devastating disease in many tropical and subtropical countries worldwide. Its pathology is caused by the eggs laid by constantly paired adult schistosome females. Without pairing, female worms remain virgin-like, or they will lose their fecundity, which includes the de-differentiation of their gonads if they have been paired but get separated from their male partners.To come closer to answers to the unsolved questions about the molecular basis of male-female interaction of schistosomes, my study aimed at the application of RNA- Seq to elucidate the transcriptomes of male and female worms of S. mansoni and, in addition, of testes and ovaries that were obtained by an organ-isolation method established in our laboratory. In this context, the effects of gender, pairing-status, and tissue-origin on gene transcription were analysed. Furthermore, based on the organ-isolation approach I isolated and characterised vitellarium tissue and vitelline cells of different differentiation stages.RNA-Seq analyses were performed on testes (T) isolated from paired (b) and unpaired (s) males (= bT, sT) and ovaries (O) from paired and unpaired females (= bO, sO), as well as their whole worm counterparts (bM, sM and bF, sF). The effects of gender, pairing-status, and tissue origin on gene expression among these samples were compared. The data sets revealed that tissue origin (organ versus worm) has a large effect on gene expression in general, which resulted in 4,534-5,478 (35% - 51%) differentially expressed genes (DEGs; 1.5-fold difference). In addition, 1,012 genes were shown to be up-regulated in all gonads compared to whole worms (> 1.5-fold change). Gene ontology analyses showed that these genes were mainly involved in processes like RNA biosynthesis, cell cycle and ribosome biogenesis, which are essential for gonad development.The number of DEGs induced by gender varied, with the lowest number of 1,445 (out of 8,590; 7.8%) for sM/sF comparison to 4,629 (out of 7,970; 41.3%) for the bT/bO comparison (1.5-fold difference). Furthermore, detailed bioinformatics analyses revealed that sF, which had never been paired before, were much closer related to males (bM or sM) than to paired females at the transcriptome level, based on the fact that 841 genes were transcribed preferentially in bM/sM/sF. This important finding sheds also new light on the question of hermaphroditism versus dioeciousness and provides a molecular fundament for the actual hypothesis of schistosome evolution and its roots originating from the Spirorchidae. In these hermaphroditic worms the male gonad develops ahead of the female gonad (protandry). This principle appears to be conserved in schistosomes as well, although apportioned to two genders.When comparing the male and female gonads, 182 and 33 genes were identified as testis- and ovary-specifically transcribed markers, respectively, which can be used in future studies as reference genes for different kinds of molecular analyses such as comparative qPCRs.Furthermore, investigating the pairing effect in detail demonstrated its fundamental impact on molecular processes in males and females, and more importantly, in their gonads. Of note, transcription of only 243 (1.4%) and 426 (1.7%) genes was influenced by pairing in testes and males, respectively. However, for ovaries and females the numbers of DEGs were 3,748 for females and 3,600 for ovaries (about 30% each). Consistent with former studies, a number of egg biosynthesis-related genes were found to be up-regulated in paired females, including egg-shell protein genes (e.g. p14 and p48) and genes encoding tyrosinases that are involved in egg-shell formation. Pairing-affected transcripts in the gonads might have functions in spermatogenesis (e.g. synaptotagmin 1 and cdc25), oogenesis (e.g. synaptotagmin 2 and cpeb), or both processes (e.g. melk).Moreover, a number of 15 genes were found to be equally transcribed among all samples, and, therefore, represented potential house-keeping genes useful in future studies.Furthermore, the RNA-Seq data also aided in the prediction in the biological context of the activities of hypothetical genes. Thus the occurrence of 238 gonad-preferentially transcribed genes indicated their hypothetical roles in testis-and/or ovary-associated functions.Finally, with the help of a modified version of the organ-isolation protocol established in our group, I succeeded in the isolation and purification of S1-S4 vitelline cells. These cells were characterized at the molecular level by RT-PCR experiments and morphologically analysed by various microscopic techniques including bright field, fluorescent, and electron microscopy. Their vitality and physiological activity was confirmed by cytological staining procedures and Ca2+-imaging analyses. It was even possible to enrich subpopulations of S1 to S4 vitelline cells by FACS analysis, which is a prerequisite for further studies. Thus S1-cell enrichment provides a basis for novel approaches towards cell-culture establishment.In summary the results obtained in my study provide novel and diverse insights into the developmental processes of the gonads as well as a broad basis for future studies aiming to unravel the role of specific factors controlling the unusual reproductive biology of schistosomes.

Die Schistosomiasis ist nach wie vor eine der bedeutendsten Infektionskrankheiten in den Tropen und Subtropen weltweit. Die Pathologie der Schistosomiasis wird durch Eier verursacht, die nur von dauerhaft gepaarten Schistosomen-Weibchen gelegt werden. Weibchen haben einen jungfräulichen Status, solange sie ungepaart sind, oder sie verlieren ihre Fertilität, wenn sie von ihrem Paarungspartner getrennt werden. Letzteres geht mit der Dedifferenzierung der Gonaden einher.Um der Frage nach der molekularen Basis der Männchen-Weibchen-Interaktion bei S. mansoni nachzugehen, zielte meine Studie auf die Durchführung von RNA-Seq-Experimenten ab, um die Transkriptome von Männchen und Weibchen sowie von Testis und Ovar zu analysieren. Diese Gonaden wurden die über eine in unserem Labor etablierte Organ-Isolationsmethode gewonnen. In diesem Zusammenhang wurden auch gewebespezifische Effekte sowie der Einfluss der Paarung auf die Gentranskription in den Gonaden analysiert. Weiterhin wurde auf Basis der Organ-Isolationsmethode Vitellarium-Gewebe gewonnen sowie Vitellinzellen charakterisiert.RNA-Seq-Experimente wurden mit Gonaden verschiedenen Ursprungs durchgeführt wie Testis (T) aus gepaarten (b) und ungepaarten (s) Männchen (= bT, sT) bzw. Ovar (O) aus gepaarten und ungepaarten Weibchen (= bO, sO) sowie zum Vergleich mit ganzen Würmern (bM, sM, bF, sF). Die Effekte des Geschlechts, des Paarungszustands und des Gewebeursprungs wurden bei der Datenauswertung verglichen. Die Ergebnisse zeigten, dass im Vergleich zum ganzen Wurm der Gewebeursprung einen beträchtlichen Effekt auf die Genexpression hat. So wurden 4,534-5,478 (35% - 51%) der insgesamt in Schistosomen vorkommenden Gene als differentiell exprimierte Gene (DEGs; > 1.5-facher Unterschied) ausgemacht. Zudem waren im Vergleich zum ganzen Wurm 1,012 Gene in den Gonaden transkriptionell hochreguliert (> 1.5-fach). Gene ontology - Analysen offenbarten, dass diese Gene hauptsächlich für Prozessen wie RNA-Synthese, Zellzyklus und Ribosomen- Biogenese von Bedeutung sind, die alle bei der Gonaden-Entwicklung eine Rolle spielen.Die Anzahl an DEGs, die durch Paarung beeinflusst wurden, variierte stark. Der niedrigste Wert von 1,445 (aus 8,590; 7.8%) wurde beim Vergleich sM/sF gefunden, der höchste Wert war 4,629 (aus 7,970; 41.3%) für bT/bO (> 1.5-fach). Weitergehende bioinformatische Untersuchungen deckten auf der Basis von 841 in bM/sM/sF gleicher- maßen transkribierten Genen auf, dass Weibchen, die niemals mit einem Männchen gepaart gewesen sind, vom Transkriptomprofil dieser 841 Gene her den Männchen (bM oder sM) ähnlicher waren als paarungserfahrenen Weibchen. Dieser Befund bringt einen neuen Aspekt in Debatte um Zwittrigkeit versus Getrenntgeschlechtlichkeit und liefert ein molekulares Fundament für die favorisierte Hypothese, dass die evolutionären Wurzeln der Schistosomen bei den Spirorchidae liegen. In diesen hermaphroditischen Würmern entwickelt sich die männliche Gonade vor der weiblichen (Protandrie). Dieses Prinzip scheint in den Schistosomen weiterhin zu bestehen, auch wenn sie zwei Geschlechter entwickelt haben.In den Gonaden selber wurden 182 bzw. 33 Gene als Testis-bzw. Ovar-spezifisch transkribiert identifiziert. Diese können in zukünftigen Studien als Referenzgene für verschiedene molekulare Analysen wie z.B. vergleichende qPCRs genutzt werden.Ferner deckte die Detailanalyse der erhaltenen Daten einen fundamentalen Einfluss der Paarung auf molekulare Prozesse in Männchen und Weibchen auf und besonders in ihren Gonaden. Bemerkenswert war hierbei, dass durch die Paarung nur 426 (1.7%) Transkripte in Männchen beeinflusst wurden sowie 243 (1.4%) der in Testis gewebe-spezifisch auftretenden Transkripte. Demgegenüber lagen die Transkript-Zahlen für Weibchen und die gewebespezifisch im Ovar auftretenden DEGs bei 3,748 in Weibchen und 3,600 im Ovar (je über 30%). In Übereinstimmung mit vorherigen Studien zeigte sich hierbei u.a., dass Eiproduktions-assoziierte Gene im Ovar gepaarter Weibchen hochreguliert waren, was Gene für Eischal-Proteine (z.B. p14 and p48) und Tyrosinasen umfasste, die an der Eischalbildung beteiligt sind. Paarungsbeeinflusste Gene wurden aber auch übereinstimmend in beiden Gonadentypen gefunden, wo sie Funktion für die Spermatogenese (z.B. synaptogagmin 1 und cdc25) wie für die Oogenese (synaptotagmin 2 und cpeb) oder für beide Prozesse (z.B. melk) ausüben könnten. Darüber hinaus wurden 15 Gene entdeckt, die in allen Proben auf gleichem Niveau transkribiert wurden und somit potentielle house-keeping Funktionen erfüllen, was ebenfalls für zukünftige Experimente von Wert sein kann.Ferner gaben die RNA-Seq-Daten auch erste Hinweise auf den biologischen Kontext, in dem die Aktivitäten vorhergesagter Gene (hypothetical proteins) zu sehen sind. So deutete das Auftreten von 238 Gonaden-präferentiell transkribierter Gene auf ihre möglichen Funktionen in Testis und/oder Ovar hin.Mit Hilfe einer modifizierten Version des Organ-Isolationsprotokolls ist es mir schließlich auch gelungen, S1-S4 Vitellinzellen zu isolieren und aufzureinigen. Diese Zellen wurden mit RT-PCRs molekular charakterisiert und über verschiedene mikroskopische Techniken, die Lichtmikroskopie, Fluoreszenz- und Elektronen-mikroskopie umfassten, analysiert. Ihre Vitalität und physiologische Aktivität wurden über cytologische Färbungen and Ca2+-imaging bestätigt. Es war sogar möglich, Subpopulationen von S1- bis S4-Zellen über FACS anzureichern, eine Voraussetzung für Folgestudien. So stellt z.B. die Anreicherung der Mitose-kompetenten S1-Zellen eine Basis für neue Ansätze zur Etablierung einer Zellkultur dar.Zusammengefasst liefern die Resultate meiner Untersuchungen neuartige und vielfältige Erkenntnisse zu Entwicklungsprozessen in den Gonaden sowie eine breite Grundlage für zukünftige Studien mit dem Ziel, die Rolle spezifischer Faktoren zu untersuchen, die die ungewöhnliche Reproduktionsbiologie der Schistosomen steuern.
Keywords: ddc:570